Community mediation in Malaysia: challenges and prospects - Abdul Hak, Nora; Ambaras Khan, Hanna; Ambaras Khan, Mushera Bibi (2014)
The efforts of the Government of Malaysia in maintaining harmony in the society began from the Independence Day. The mandate to maintain harmony was given to the Department of National Unity and Integration Malaysia, one of the departments under the Prime Minister Office. In 2007, the Department introduced community mediation programme. The mediators are the Rukun Tetangga (Peaceful Neighbourhood)Committee. The purpose of Rukun Tetanggais to empower the people to resolve the problems facing by them in their neighbourhood amicably. The Department has trained 874 community mediators. The programme is important to ensure all issues involving different racial and religious groups are handled diligently to avoid any inter-racial and intra-racial tension. Various efforts have been made to ensure the success of the program. There are however, rooms to improve this programme. The objective of this paper is to study the laws pertaining to this programme. Currently, The Mediation Act 2012 is the laws applicable to mediation practice in Malaysia. The authors suggest that the community mediators’ training module is to be amended by the Department of National Unity and Integration Malaysia to incorporate the content and spirit of the Mediation Act 2012 in its training module